2022
DOI: 10.5194/bg-19-4521-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the presence of plateau pikas on the ecosystem services of alpine meadows

Abstract: Abstract. The activity of small mammalian herbivores influences grassland ecosystem services in arid and semi-arid regions. Plateau pika (Ochotona curzoniae) was considered to be a focal organism to investigate the effect of small mammalian herbivores on meadow ecosystem services in alpine regions. In this study, a home-range scale was used to measure the forage available to livestock, water conservation, carbon sequestration and soil nutrient maintenance (total nitrogen, phosphorus and potassium) in the topso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition, plateau zokors (Eospalax baileyi) and plateau pika (Ochotona curzoniae) are abundant in the Yellow River source area [19]. As essential sources of biological disturbance in alpine meadow ecosystems, their digging and gnawing behaviors not only have a significant impact on vegetation and soil [20][21][22], but the loose mounds formed by their mounding can also directly form secondary bald patches of bare ground, as well as provide material sources for soil erosion [23][24][25]. Many scholars have shown that meadow degradation is closely related to the degree of development of bald patches, and soil erosion after meadow degradation positively influences further soil erosion and meadow degradation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plateau zokors (Eospalax baileyi) and plateau pika (Ochotona curzoniae) are abundant in the Yellow River source area [19]. As essential sources of biological disturbance in alpine meadow ecosystems, their digging and gnawing behaviors not only have a significant impact on vegetation and soil [20][21][22], but the loose mounds formed by their mounding can also directly form secondary bald patches of bare ground, as well as provide material sources for soil erosion [23][24][25]. Many scholars have shown that meadow degradation is closely related to the degree of development of bald patches, and soil erosion after meadow degradation positively influences further soil erosion and meadow degradation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Although species richness is related to floristic composition and plays a vital role in succession (Moog et al, 2002) and stability of a grassland community (Fischer et al, 2016), the effects of foragingtunnel disturbances on richness have received little attention. Thomas, 1911) is a common subterranean herbivorous mammal native to alpine grasslands in the Qinghai-Tibetan Plateau (Tang et al, 2010;Zhang et al, 2014;Liu et al, 2022), a grassland that sustains yak and Tibetan sheep production (Yang et al, 2019) and is also the habitat of some endemic species (Chen et al, 2022). Plateau zokors, with 15-25 cm length and 200-480 g weight, usually spend almost their entire lifetime underground (Chu et al, 2020;Niu et al, 2020) and, similar to pocket gophers in prairies (Steuter et al, 1995), feed on plant below-ground tissues in extensive foraging tunnels at depths of 3-20 cm.…”
Section: Introductionmentioning
confidence: 99%
“…At present, along with the phenomenon of meadow vegetation degradation and soil degradation, which also provides a good vision and site for the activities of plateau rodents, the local government's early rodent extermination behavior has seriously affected the number of their predators, resulting in a continuous surge in their populations and an expansion of their activity range in recent years. In addition, although the activities of these rodents may have some positive effects on soil air circulation, nitrogen cycling, and vegetation community restoration, their burrowing and gnawing behaviors disrupt the natural vegetation community features and soil structures of alpine meadows [8][9][10], and the accumulated loose mounds indirectly form secondary bald patches of land and supply a material source for soil erosion [11,12]. So far, many scholars have concluded that rodent activity-induced meadow degradation areas stimulate soil erosion under various wind, water, or freeze-thaw dynamics and generate or exacerbate other natural hazards [13,14], negatively affecting the sustainability and security of the whole alpine meadow ecosystem [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape patterns are the consequence of coupling diverse ecological processes [16], and studying the spatial pattern changes in landscape patches is significant to understand the soil degradation and vegetation degradation mechanisms [17,18]. The source zone of the Yellow River is influenced by rodent activities [19], and the landscape fragmentation is severe, among which the rodent mound patches formed by plateau pika activities lead to the reverse succession of the meadow ecosystem, which has a specific impact on community habitat texture heterogeneity, species diversity, and soil erodibility [9,20,21]. Landscape indices are quantitative indicators that reflect the structural composition and spatial configuration of the landscape, which serve as a bridge between landscape patterns and ecological processes [22], and currently, with the advancement of 3S technology and landscape ecology, studies on the effects of soil erosion based on landscape indices have been widely carried out [23][24][25].…”
Section: Introductionmentioning
confidence: 99%